EFFICIENCY OF ACCOUNTING CONSULTING IN IT COMPANIES AND THE CURRENT DEVELOPMENT OF INFORMATION TECHNOLOGY - Myronchuk, Z.; Tsitska, N.; Andruchko, R.; Maletska, O. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The primary focus of this scientific article is to comprehensively examine the nature and potential growth of accounting consulting within the realm of IT enterprise management. Specifically, the research aims to uncover the theoretical principles and real-world implications of accounting consulting and to evaluate its influence on the financial stability and efficacy of an enterprise. The current trends, advantages and disadvantages of using information technologies in the modern world, their development and application in agriculture are substantiated. Having analyzed the data on the structure of the consulting market in Ukraine by segments, it is found that accounting consulting occupies a prominent place in the market of consulting services in Ukraine and is one of the important elements of doing business in the modern world. The article examines how actively companies use IT technologies and innovative solutions, as well as the provision of accounting advice by various consulting companies, both foreign and domestic. It is noted that the activities of IT companies are considered to be very specific compared to other types of services. This fact is confirmed by legislative acts not only in Ukraine but also in other countries of the world and Europe. The article considers the peculiarities of the taxation system, rules of profit taxation and certain types of benefits for IT companies, problems of licensing of accounting consulting companies, as well as services provided by consulting firms. The authors suggest ways of developing consulting companies in Ukraine. It is predicted that in the future, accounting consulting in the IT sector will continue to integrate modern technologies and will focus on analytics and strategic management.